The significance of sound from the perspectives of islam and multimedia / Rozeleenda Abdul Rahman …[et al.] - Abdul Rahman, Rozeleenda; Che Hassan, Nurul Hidayah; Ismail, Juhaida; Noradzan, Haslinda; Abdul Razak, Nawal (2016)
Sound is the most sensuous element in human life. It is the only main form of communication besides body languages. For instance, in learning environment, it is highlighted that audible materials used in classrooms can enhance student's listening skills, as sound can inspire them to retain the information longer. Besides, in marketing, sound is also critical in developing brand and multimedia titles to promote products by providing a creative content in a distinctive way. Here, there have been promising advantages in utilizing sound in our productions and contents development, however, most of the research highlights primarily on the usage of this element in only several areas, such as education, advertising, entertainment and theraphy. Unfortunately less consideration has been given to the use of sound from the religious perspectives. Thus, in this paper we will explore the significance of sound in the religious perspectives, specifically in the religious activities, and identify the similarities with the multimedia usage. In our work, we use Islam as the religious context. We will look into the importance of incorporating sound reffering to the Holy Qur'an, as many verses have been mentioned hearing and the ears that related to sound are more important than the eyes and the heart. In this study, besides reviewing the literatures, we arranged interviews with prominent Islamic scholars from Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi Mara Cawangan Pahang (Kampus Raub). Based on the inputs, we will compare and make a contribution to a better understanding of the powerful aspects of sound element from both perspectives; Islam and multimedia.